Demonstration of a full-scale plant using an UASB followed by a ceramic MBR for the reclamation of industrial wastewater. (October 2016) - Niwa, Terutake; Hatamoto, Masashi; Yamashita, Takuya; Noguchi, Hiroshi; Takase, Osamu; Kekre, Kiran A.; Ang, Wui Seng; Tao, Guihe; Seah, Harry; Yamaguchi, Takashi
Highlights: A full-scale UASB reactor followed by a ceramic MBR was demonstrated for 395 days. The system achieved a power consumption of 0.76 kWh m −3 during 25 LMH operation. Bacteria in the UASB reactor adopted to treat this mixed industrial wastewater. Ceramic membrane completely recovered TMP by cleaning after 395 days operation. Abstract: This study comprehensively evaluated the performance of a full-scale plant (4550 m 3 d −1 ) using a UASB reactor followed by a ceramic MBR for the reclamation and reuse of mixed industrial wastewater containing many inorganics, chemical, oil and greases. This plant was demonstrated as the first full-scale system to reclaim the mixed industrial wastewater in the world. During 395 days of operation, influent chemical oxygen demand (COD) fluctuated widely, but this system achieved COD removal rate of 91% and the ceramic MBR have operated flux of 21–25 LMH stably. This means that this system adsorbed the feed water fluctuation and properly treated the water. Energy consumption of this plant was achieved 0.76 kWh mm −3 and this value is same range of domestic sewage MBR system. The combination of an UASB reactor and ceramic MBR is the most economical and feasible solution for water reclamation of mixed industrial wastewater.